Trust based multipath qos routing protocol for mission-critical data transmission in tactical ad-hoc networks - Keum, Dooho; Lim, Jihun; Ko, Young Bae (Sensors (Switzerland), 2020)
In tactical ad-hoc networks, the importance of various tactical sensors and mission-critical data is increasing owing to their role in determining a tactical situation and ensuring the viability of soldiers. In particular, the reliability of mission-critical data has to be ensured for accurate situation determination and decision making. However, managing the network and trustworthiness in an environment where malicious nodes exist and a large amount of mission-critical data occur is a challenging issue. To solve these issues, a routing protocol is needed that can effectively detect malicious nodes and ensure the reliability and quality of service (QoS) of mission-critical data. In this paper, we propose a trust-based multipath QoS routing protocol (called MC_TQR) for tactical ad-hoc networks that can detect malicious nodes and satisfy the requirements of mission-critical data. The proposed scheme is verified using an OPNET simulator, and the results confirm the improved network performance when compared with existing schemes.
Keywords: Large amounts; Malicious nodes; Mission critical; Multipath; OPNET simulator; QoS routing protocol; Tactical ad hoc networks; Mission-critical data; Tactical ad-hoc network; Trust-based multipath QoS routing